The law of political economy : transformations in the function of law / edited by Poul F. Kjaer. - Kjaer, Poul F. (Cambridge University Press, 2020)
This book develops the law of political economy as a new field of scholarly enquiry. Bringing together an exceptional group of scholars, it provides a novel conceptual framework for studying the role of law and legal instruments in political economy contexts, with a focus on historical transformations and central challenges in both European and global contexts. Its chapters reconstruct how the law of political economy plays out in diverse but central fields, ranging from competition and consumer protection law to labour and environmental law, giving a comprehensive overview of the central challenges of the law of political economy. It also provides a sophisticated and multifaceted framework for further enquires while outlining the contours of new law of political economy.